Performance of Shisham (Dalbergia sissoo Roxb.) Provenances Against Ganoderma Root Rot - Sharma, R. C.; Pal, Mohinder; Singh, Ranjeet (Indian Forester, 2010)
Forty provenances of Shisham (Dalbergia sissoo) were screened against Ganoderma root rot under the natural conditions in a randomized block design. Variations to the extent of mortality and plants showing initial root rot symptoms were recorded. None of the provenance remained disease free. However, least mortality (2.0%) was recorded in Barielly provenance followed by 4.2 per cent in Rampur provenance and rated as resistant to Ganoderma root rot. In the plantation of Rampur and Barielly provenances, 4.2 and 10.4 per cent plants, respectively showed initial symptoms of root rot. Highest mortality (33.4%) was recorded in Banaras provenance followed by 29.2 per cent in each Nazibabad and Etawah provenances. In terms of height and diameter, Kankai provenance was rated as best but it was moderately susceptible (14.6% tree mortality) to Ganoderma root rot. Provenance Rampur, which was rated as resistant with 2.0 per cent tree mortality, was fifth best in terms of plant height and diameter at breast height